2018
DOI: 10.1002/ejic.201800897
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Corroles with Bis‐Ammonia or Mono‐DMSO Axial Ligands. Electrochemical, Spectroscopic Characterizations and Ligand Binding Properties

Abstract: Four bis-ammonia ligated cobalt corroles and four mono-DMSO ligated cobalt corroles with different meso-aryl substituents on the macrocycle (A 2 B-and A 3 -corroles) were synthesized and investigated as to their electrochemical and spectroscopic properties under different solution conditions. The complexation energies of the investigated cobalt corroles were [a] Scheme 2. Structures of the investigated bis-ammonia and mono-DMSO meso-aryl cobalt corroles. dinated form of A 3 -and/or A 2 B-cobalt corroles) whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 27 publications
7
47
0
Order By: Relevance
“…Although the same final [(Ar) 3 CorCo II ] − product is formed in both cases, the difference in thermodynamic half-wave potentials for the one-electron addition can be significant, varying by as much as 1.0 V depending on the type of axial ligand and specific Ar substituents. 38,48,58 One problem with elucidating the effect of axial coordination on the redox potentials of hexacoordinate cobalt corroles is the lability of the axial ligand(s) in solution, which results in a concentration-dependent complexation where one, or both, ligands dissociate in dilute solutions. In search of nonlabile coordinating ligands, we recently investigated the possible binding of anionic ligands to neutral cobalt triarylcorroles and found that 10 of the 11 investigated anionic ligands (PF 6 − , BF 4 − , HSO 4 − , ClO 4 − ,B r − ,I − ,C l − , OAc − ,F − , OTs − ) were unable to bind to the cobalt center of the neutral complex, with the only exception being CN − , where a stepwise formation of both mono-and bis-CN adducts was observed in solutions of CH 2 Cl 2 (eqs 3 and 4).…”
Section: Introductionmentioning
confidence: 99%
“…Although the same final [(Ar) 3 CorCo II ] − product is formed in both cases, the difference in thermodynamic half-wave potentials for the one-electron addition can be significant, varying by as much as 1.0 V depending on the type of axial ligand and specific Ar substituents. 38,48,58 One problem with elucidating the effect of axial coordination on the redox potentials of hexacoordinate cobalt corroles is the lability of the axial ligand(s) in solution, which results in a concentration-dependent complexation where one, or both, ligands dissociate in dilute solutions. In search of nonlabile coordinating ligands, we recently investigated the possible binding of anionic ligands to neutral cobalt triarylcorroles and found that 10 of the 11 investigated anionic ligands (PF 6 − , BF 4 − , HSO 4 − , ClO 4 − ,B r − ,I − ,C l − , OAc − ,F − , OTs − ) were unable to bind to the cobalt center of the neutral complex, with the only exception being CN − , where a stepwise formation of both mono-and bis-CN adducts was observed in solutions of CH 2 Cl 2 (eqs 3 and 4).…”
Section: Introductionmentioning
confidence: 99%
“…With the intention to provide the cobalt central atom of complex 1 in a low oxidation state to foster the hydrogenation process, [12a] we conducted the nitrobenzene reduction in the presence of solid reducing agents such as Zn, Mn, and Mg. Rewardingly, the pertinent reaction also proceeded well without external reductants and moreover, the catalytic system did not benefit in any way from the addition of acids or bases (Table S4). If ammonia was added to a solution of 1 in ethanol, formation of the known bis(ammine) cobalt corrole complex was observed [25b] which, however, proved to be inactive in the target transformation. These experimental findings provided compelling reasons that the given Co‐catalyzed nitroarene hydrogenation is best performed without any additives.…”
Section: Resultsmentioning
confidence: 99%
“…Tetrakis(4-ethynylphenylmethane) 2, 55 corrole 1 59 and metallocorrole 3 37 were prepared according to previously published procedures. Additional information is given in the Supporting Information.…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…ammonia acting as a protecting group. 37 Interestingly, ammine ligands are sufficiently labile to be easily removed by gentle heating under vacuum to lead to the "active" tetracoordinated cobalt corroles without any bound ligand in apical position. Such square planar complex constitutes the active species of cobalt corroles for CO bonding on the metal center.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation